Evidence for Secondary Ice Production in Southern Ocean Maritime Boundary Layer Clouds - Järvinen, Emma; McCluskey, Christina S.; Waitz, Fritz; Schnaiter, Martin; Bansemer, Aaron; Bardeen, Charles G.; Gettelman, Andrew; Heymsfield, Andrew; Stith, Jeffrey L.; Wu, Wei; D’Alessandro, John J.; McFarquhar, Greg M.; et al. (John Wiley and Sons, 2022)
Maritime boundary-layer clouds over the Southern Ocean (SO) have a large shortwave radiative effect. Yet, climate models have difficulties in representing these clouds and, especially, their phase in this observationally sparse region. This study aims to increase the knowledge of SO cloud phase by presenting in-situ cloud microphysical observations from the Southern Ocean Clouds, Radiation, Aerosol, Transport Experimental Study (SOCRATES). We investigate the occurrence of ice in summertime marine stratocumulus and cumulus clouds in the temperature range between 6 and −25°C. Our observations show that in ice-containing clouds, maximum ice number concentrations of up to several hundreds per liter were found. The observed ice crystal concentrations were on average one to two orders of magnitude higher than the simultaneously measured ice nucleating particle (INP) concentrations in the temperature range below −10°C and up to five orders of magnitude higher than estimated INP concentrations in the temperature range above −10°C. These results highlight the importance of secondary ice production (SIP) in SO summertime marine boundary-layer clouds. Evidence for rime splintering was found in the Hallett-Mossop (HM) temperature range but the exact SIP mechanism active at lower temperatures remains unclear. Finally, instrument simulators were used to assess simulated co-located cloud ice concentrations and the role of modeled HM rime-splintering. We found that CAM6 is deficient in simulating number concentrations across the HM temperature range with little sensitivity to the model HM process, which is inconsistent with the aforementioned observational evidence of highly active SIP processes in SO low-level clouds.